2016
DOI: 10.1016/j.hrthm.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

J-wave duration and slope as potential tools to discriminate between benign and malignant early repolarization

Abstract: (AAM) is copyrighted and published by Elsevier. It is posted here by agreement between Elsevier and the University of Turin. Changes resulting from the publishing process-such as editing, corrections, structural formatting, and other quality control mechanisms-may not be reflected in this version of the text. The definitive version of the text was subsequently published in HEART RHYTHM, 13 (3), 2016, 10.1016/j.hrthm.2015.11.029. You may download, copy and otherwise use the AAM for non-commercial purposes provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As ER has been related to increased incidence of sudden cardiac arrest in healthy young adults, there has been increasing interest in understanding the clinical significance of J waves. The concept of “benign” versus “malignant” J waves has been described in the young healthy population and was associated with a higher risk of sudden death . However, we did not comment on the “type” of J waves in our cohort given the lack of reports confirming these data.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As ER has been related to increased incidence of sudden cardiac arrest in healthy young adults, there has been increasing interest in understanding the clinical significance of J waves. The concept of “benign” versus “malignant” J waves has been described in the young healthy population and was associated with a higher risk of sudden death . However, we did not comment on the “type” of J waves in our cohort given the lack of reports confirming these data.…”
Section: Discussionmentioning
confidence: 78%
“…) and () present in at least two consecutive leads, as previously defined and published by Macfarlane et al. and Cristoforetti et al . We did not consider ST segment elevation nor T‐wave amplitude while interpreting the presence of J waves and/or measuring its amplitude.…”
Section: Methodsmentioning
confidence: 99%
“…Such was not the case here. Other significant risk factors were absent: QTc was not >400 ms, T/R ratio was not <0.25 in V5, and J‐wave duration was not >60 ms (Cristoforetti et al., ; Roten et al., ). The association of ER with arrhythmic risk is typically at rest or during sleep, and not during physical activity (Obeyesekere et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Cristoforetti et al suggested that a duration > 60 milliseconds is a marker of increased risk of VF (P<0.001). 73 Additional studies have sought to investigate if the localization of the J-wave is of any importance and have concluded that global J-waves in both inferior and lateral leads are associated with the highest risk of arrhythmic events (odds ratio 4.87, 95% CI: 2.64-9.01, P < 0.00001), 67 followed by J waves in inferior leads (hazard ratio 3, 95% CI 1.45-5.89 P<0.01). 55 Other ECG findings that have been investigated include the STsegment and the T-wave.…”
Section: Delineating the Identikit Of Malignant Ermentioning
confidence: 99%